Painful muscle spasms complicating algodystrophy: central or peripheral disease?. Issue 4 (April 1988) - Robberecht, W; Van Hees, J; Adriaensen, H; Carton, H
Abstract : A 21 year old female patient developed Südeck's atrophy of the right foot secondary to a chronic Achilles tendinitis. The condition was complicated by the occurrence of painful muscle spasms in the right leg and incontinence of urine. The spasms had characteristics of both a tonic ambulatory foot response and a spinal flexor reflex. The movements disappeared during sleep. Regional anaesthesia of the right leg made the spasms disappear both in and outside the region of anaesthesia. Backaveraging of the EEG showed the involuntary spasms to be preceded by a cortical potential similar to a readiness potential, indicating a cortical potential similar to a readiness potential, indicating a cortical component in the pathophysiology of the muscle spasms complicating Südeck's atrophy.